Nervous System-Systemic Crosstalk in SARS-CoV-2/COVID-19: A Unique Dyshomeostasis Syndrome - Anand, Harnadar; Ende, Victoria; Singh, Gurinder; Qureshi, Irfan; Duong, Tim Q.; Mehler, Mark F. (Frontiers in Neuroscience, 2021)
SARS-CoV-2 infection is associated with a spectrum of acute neurological syndromes. A subset of these syndromes promotes higher in-hospital mortality than is predicted by traditional parameters defining critical care illness. This suggests that deregulation of components of the central and peripheral nervous systems compromises the interplay with systemic cellular, tissue and organ interfaces to mediate numerous atypical manifestations of COVID-19 through impairments in organismal homeostasis. This unique dyshomeostasis syndrome involves components of the ACE-2/1 lifecycles, renin-angiotensin system regulatory axes, integrated nervous system functional interactions and brain regions differentially sculpted by accelerated evolutionary processes and more primordial homeostatic functions. These biological contingencies suggest a mechanistic blueprint to define long-term neurological sequelae and systemic manifestations such as premature aging phenotypes, including organ fibrosis, tissue degeneration and cancer. Therapeutic initiatives must therefore encompass innovative combinatorial agents, including repurposing FDA-approved drugs targeting components of the autonomic nervous system and recently identified products of SARS-CoV-2-host interactions.